Ragam Persepsi Halâlan Thayyiban pada Kuliner Khas Minangkabau - Hidayatul Azizah Gazali; Sefri Auliya (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The Minangkabau people believe that ABS-SBK is a philosophy of life, which has been implemented in all segments of life, including food. However, in reality on the ground, it was found that that producers and consumers of Minangkabau culinary had different understandings regarding the concept of halâlan tayyib. Only a small number of typical Minang culinary producers and consumers understand the concept of halâlan tayyib in the Al-Qur'an, including their knowledge of the verses, meanings, and contents. Understanding the concept of halâlan tayyib will have a big influence on the Minang culinary processing process. This research aims to identify the diversity of Minangkabau people's understanding of halâlan tayyib food and drinks. This research is field research using a qualitative approach with analytical descriptive methods using perception theory. The results of this research show that producers and consumers of Minangkabau culinary have varying perceptions of halâlan thayyiban concepts according to the cognitive, affective and conative components that formed their perceptions